2010
DOI: 10.1016/j.acuro.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Sistema REMEEX® para el tratamiento de la incontinencia de esfuerzo masculina: nuestra experiencia

Abstract: The REMEEX® system for the treatment of male SUI presents (in our experience) a 75% of good results (continent patients or patients with light urinary incontinence) at the year of follow-up with a high rate of light complications. Readjustment are frequent at the first six months after intervention and it's necessary an intense follow-up. We need more studies that evaluate the long-term efficiency of this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
6
2
1
Order By: Relevance
“…Though the effectiveness of or results is similar to previous studies [ 6 , 12 , 13 , 14 ], in said studies, the rate of complete dry patients (0–1 safety pads) varies from 36%–64.7% compared to the 72.34% found in our study. This could be due to the fact that, as years go by, the technique of the surgical procedure has been further standardized, allowing for better results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Though the effectiveness of or results is similar to previous studies [ 6 , 12 , 13 , 14 ], in said studies, the rate of complete dry patients (0–1 safety pads) varies from 36%–64.7% compared to the 72.34% found in our study. This could be due to the fact that, as years go by, the technique of the surgical procedure has been further standardized, allowing for better results.…”
Section: Discussionsupporting
confidence: 91%
“…Our results show that our sample comprised male patients with a mean age of 69.76 years, which was also observed in previous studies where the mean age was between 67–70.4 years [ 6 , 7 , 8 , 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The retropubic permanent suture passage was associated with a 10% bladder perforation rate, 6% infection/erosion, and 86% required at least 2 adjustment revisions. Findings were similar to Jimenez Parra et al [ 47 ], in their small series of 14 patients published in 2010, they reported a 21% explantation rate, 29% bladder perforation, and 36% urinary retention. At a mean follow-up of 18.6 months 42% of patients were totally continent and 33% reported light incontinence.…”
Section: Surgical Treatment Of Ppisupporting
confidence: 88%
“…Results of initial and longer-term followup demonstrate success rates of 13–100% with larger series reporting rates of 54–79% [45, 4752]. Patients required adjustments in 10–100% of cases, many of which required repeated anesthesia.…”
Section: Resultsmentioning
confidence: 99%